Disruption Tolerance Index for determining household susceptibility to infrastructure service disruptions. (July 2021) - Esmalian, Amir; Coleman, Natalie; Yu, Simon; Koceich, Madison; Esparza, Miguel; Mostafavi, Ali
Abstract: The objective of this paper is to develop household susceptibility indices related to disruptions in infrastructure services during disasters. The prolonged disruptions in infrastructure services create great hardship for the households of a community affected by natural hazards, especially shelter-in-place households who are at a high risk of such disruptions. The literature currently lacks tools and methods to assist decision makers in considering the tolerance and susceptibility of the household in communities to the infrastructure service disruptions. While there are some vulnerability indices in the disaster literature, the scores have not developed to specifically consider the risks associated with the infrastructure service disruptions. Hence, in this study, we developed and implemented Disruption Tolerance Index (DTI) to enable understanding of spatial patterns of susceptibility to service disruptions. In particular, we create susceptibility scores and maps for disruptions in power and transportation systems as two essential services on which households rely during their daily life. These service disruptions include power outages and road closures due to the natural hazards which disrupted households' access to these services. The factors for determining DTI scores are selected through an empirical analysis of households' susceptibility to the disruptions, the scores are calculated by implementing Principal Components Analysis, and the scale of the scores is discussed. The study reveals the hot spots and cold spots of compound susceptibility to the disruptions. Unveiling the spatial clusters of susceptibility provides decision makers with the necessary information to consider the households' susceptibility in emergency plans and risk mitigation practices. The approach developed in this study could be adapted for different locations to enable understanding of the unique susceptibility of the households from the infrastructure services during disasters. Such understanding provides the decision-makers with the essential information to plan and mitigate the risk mitigation approaches and preparedness actions related to the risks associated with infrastructure service disruptions.